0
$\begingroup$

Consider a Poisson process with rate $\lambda$ and let $L$ be the time of the last arrival in the interval $[0,t]$, with $L=0$ if there was no arrival.

How can I prove that t-L has exponential distribution with rat $\lambda$? I tried to prove it by the following relation \begin{equation} P(t-L>x)=P(N(x)=0) \end{equation} However it leads us to a correct answer but I think this relation can not be true. because $P(N(x))=0$ doesn't have any information about t! Actually we know that $t-L>x$ means that $N(x)=0$ but the reverse is not obvious.So all we can say is: $P(t-L>x)<=P(N(x)=0)$. The purpose of this discussion is to find $E[t-L]$ by the knowledge of distribution of $L$ or $t-L$!

$\endgroup$
2
  • $\begingroup$ I seem to remember an answer that Did (a very high-reputation user on math.SE) posted on math.SE to the effect that while the time of the next arrival after any given time $t_0$ is indeed exponentially distributed, the time of the most recent arrival before $t_0$ is not exponentially distributed. But I don't seem to be able to find that answer now. $\endgroup$ Commented Oct 18, 2015 at 22:05
  • $\begingroup$ The answer referred to in my comment above might be this one where the time elapsed since the last arrival is claimed to be of the form $\min(t,X)$ where $X$ is an exponential random variable with parameter $\lambda$ (while as everyone knows and agrees that the time till the next arrival after $t$ is exponentially distributed with parameter $\lambda$). $\endgroup$ Commented Oct 18, 2015 at 22:22

2 Answers 2

0
$\begingroup$

Let us define a random variable T=t-L

$P(T<x)$ $\\=1-P(\text{no arrival happened in the interval } [t-x, t])$ $\\= 1-P(\text{no arrival happened in the interval } [0, x])$ $\\= 1-\frac{\lambda^0}{0!} \exp{(-\lambda x)}$ $\\= 1-\exp{(-\lambda x)}$

This is the cdf of the exponential distribution.

$\endgroup$
5
  • $\begingroup$ Consider the case that there is an arrival between L and t-x but there is no.arrival between t-x and t. So your first equality is not true! $\endgroup$ Commented Oct 11, 2015 at 17:59
  • $\begingroup$ What do you mean there is an arrival between L and t-x? Wasn't L defined as the last arrival? $\endgroup$
    – michal
    Commented Oct 11, 2015 at 18:40
  • $\begingroup$ what you said is: $P(t-L>x)=P(no~ arrival~ in ~[t-x,t])$. we know that if $A\Rightarrow B$ then $P(A)\le P(B)$.in our discussion we know that $t-L>x\Rightarrow no~ arrival ~in~ [t-x, t]$ so $P(t-L>x)\le P(no~ arrival ~in [t-x,t])$ but $no ~arrival ~in [t-x,t]$ doesn't mean $t-L>x$ or equivalently $L<t-x$. I mean the reverse is not true. $\endgroup$ Commented Oct 12, 2015 at 6:26
  • $\begingroup$ That is not true what you said. P(t-L > x) only says about what happens in the subinterval [t-x, t]. The second implication holds too. $\endgroup$
    – michal
    Commented Oct 12, 2015 at 11:01
  • $\begingroup$ x is bounded. The last period T does not follow exponential distribution, because the period between L and next arrive will be the exponential distribution, and T is always less than this period. $\endgroup$
    – Tony416
    Commented Sep 10, 2020 at 23:29
0
$\begingroup$

My Professor (Dr.Pasha) has guided me to solve the problem as follows: Theorem 2.14.(Richard Durrett) If we condition on N(t), then $T_1,T_2,..,T_n$ have uniform distribution in [0,t]. thus $P(\max \{T_1,...,T_n\}<s)=\frac{s^n}{t^n}$ so $E[L|N(t)=n]=\frac{nt}{n+1}$

$E [L] = \sum_{n=0}^{\infty} E [ L \,| \, N(t) = n ] \, P \{ N(t)=n \} =\sum_{n=0}^{\infty} E [\max \{T_1,...,T_n\}\,| \, N(t) = n ] \, P \{ N(t)=n \} = \sum_{n=0}^{\infty} \frac{n t}{n+1} \, P \{ N(t)=n \} = \sum_{n=0}^{\infty} \left( 1 - \frac{1}{n+1} \right) t \, \frac{ (\lambda t)^n}{n!} e^{-\lambda t} = t e^{- \lambda t} \sum_{n=0}^\infty \frac{(\lambda t)^n}{n!} - t e^{- \lambda t} \sum_{n=0}^\infty \frac{1}{n+1} \frac{ ( \lambda t)^n}{n!}.$\

Now after a little computation you find that

$\sum_{n=0}^\infty \frac{1}{n+1} \frac{ ( \lambda t)^n}{n!} = \frac{1}{ \lambda t} ( e^{ \lambda t} - 1 ).$\

Thus

$E [ L ] = t - t e^{- \lambda t} \frac{1}{\lambda t} ( e^{ \lambda t} - 1 ) = t - \frac{1}{\lambda } (1 - e^{ \lambda t} ).$

Therefore we indeed obtain

$E [ t - L ] = t - E [ L ] = t - \left( t - \frac{1}{\lambda } (1 - e^{ \lambda t} ) \right) = \frac{1}{\lambda } (1 - e^{ \lambda t} ).$

$\endgroup$
1
  • $\begingroup$ So what was wrong with my answer? $\endgroup$
    – michal
    Commented Oct 19, 2015 at 15:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.